Mengoptimalkan Peran Pondok Pesantren Dalam Pendidikan Islam - Mardiah Astuti; Herlina Herlina; Ibrahim Ibrahim; Aldi Junandar; M. Bagus Prasetyo; Dini Marega (Jurnal Kajian dan Penelitian Umum, 2023)
An article entitled optimizing the role of Islamic boarding schools in Islamic education. This article describes the role of Islamic boarding schools as learning centers that are rich in Islamic religious values, traditions and culture. Islamic boarding schools do not only focus on academic aspects, but also on the formation of students' character and morals. By combining theoretical teaching with the practice of daily life, Islamic boarding schools create an environment that supports the holistic development of students. In order to optimize the role of Islamic boarding schools in Islamic education, continuous efforts are needed. By strengthening the curriculum, increasing collaboration, leveraging technology, and involving the community, Islamic boarding schools can continue to be relevant educational institutions.